2021
DOI: 10.1002/jobm.202100101
|View full text |Cite
|
Sign up to set email alerts
|

High‐level production of microbial prodigiosin: A review

Abstract: Prodigiosin is a natural red pigment derived primarily from secondary metabolites of microorganisms, especially Serratia marcescens. It can also be chemically synthesized. Prodigiosin has been proven to have antitumor, antibacterial, antimalaria, anti‐insect, antialgae, and immunosuppressive activities, and is gaining increasing important in the global market because of its great potential application value in clinical medicine development, environmental treatment, preparation of food additives, and so on. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 122 publications
1
20
0
Order By: Relevance
“…Interestingly, extending the cultivation time to 48 h resulted Molecules 2022, 27, 3729 4 of 18 in a slightly higher biopigment production only in FB medium (11.1 mg/L), which has the highest peptone content, while in other media a decrease in the biopigment concentration was noticed. Previously, peptone and yeast extract were found to be the best carbon and nitrogen sources for S. marcescens to produce PG [46], while other studies showed that glycerol plays an important role as a carbon source [47]. Beyond 48 h, prolonged cultivation time resulted in an overall PG decrease in each medium, due to the depletion of nutrients and possible degradation of PG.…”
Section: S Marcescens Atcc 27117 Cultivation For Prodigiosin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, extending the cultivation time to 48 h resulted Molecules 2022, 27, 3729 4 of 18 in a slightly higher biopigment production only in FB medium (11.1 mg/L), which has the highest peptone content, while in other media a decrease in the biopigment concentration was noticed. Previously, peptone and yeast extract were found to be the best carbon and nitrogen sources for S. marcescens to produce PG [46], while other studies showed that glycerol plays an important role as a carbon source [47]. Beyond 48 h, prolonged cultivation time resulted in an overall PG decrease in each medium, due to the depletion of nutrients and possible degradation of PG.…”
Section: S Marcescens Atcc 27117 Cultivation For Prodigiosin Productionmentioning
confidence: 99%
“…This yield was almost 2-fold lower than that achieved in flasks (Figure 3) but leaves room for further optimization. Indeed, usually fed-batch fermentation was found to be optimal for PG as well as some other biopigments production [10,46,52]. For example, by optimizing culture medium using brown sugar or cassava wastewater as low-cost carbon sources in a 5 L agitator bioreactor, yields of 8.1 g/L and 6.1 g/L were achieved, respectively [49,53].…”
Section: S Marcescens Atcc 27117 Cultivation For Prodigiosin Productionmentioning
confidence: 99%
“…7,36,[46][47][48][49] It has been shown by You et al 46 that the pigC enzyme has its temperature optimum between 10 and 20 C. Other prodigiosin-producing strains such as S. marcescens have been reported to show still higher prodigiosin titers (more than 6 g/L), yet at the drawback of using an opportunistic pathogenic strain. 4 In addition to optimization of cultivation conditions, further genetic modification of P. putida strains has been shown to increase prodigiosin titers. 50 Subsequently, the space-time yield (STY) was calculated for this production process to evaluate the productivity of the process.…”
Section: Validation Of An Online Screening Protocol For Prodigiosinmentioning
confidence: 99%
“…The bright red‐colored natural product prodigiosin is a prominent member of the prodiginine class and is produced by various bacteria, including Serratia marcescens ( S. marcescens ) and Hahella chejuensis ( H. chejuensis ) 1–4 . Prodiginines exhibit various biological activities as antibiotic and antimalarial compounds, anti‐cancer compounds, autophagy modulating compounds, and compounds against plant pathogenic nematodes and fungi 5–12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation